THE EFFECT OF ADDING WASTE TIRE RUBBER POWDER ON PAVING BLOCK WEAR - Soebandono, Bagus (KURVATEK, 2024)
Pavement using paving blocks is the right choice because of its easy installation and maintenance. One form is a quadrilateral type that is widely used for environmental and pedestrian roads. With good road access being one of the improvements in vehicles so that waste tires also increase, solutions are needed to reduce the impact on the environment but are also expected to provide benefits for paving block roads, especially increasing adhesion between paving block constituent materials. Based on this background, it was a research idea with the aim of determining the effect of adding waste tire rubber powder on the wear resistance of paving blocks. Research method with strength testing on paving block samples with a size of 5 cm x 5 cm x 2 cm a total of 18 samples. The results showed the average strength value of paving blocks with a mixture of waste tire rubber of 1%, 2%, 3%, 4%, 5% of 0.134, 0.223.0235, 0.246 and 0.247 mm / minute, so that the addition of waste tire rubber powder showed a decrease in the wear rate of paving blocks.